Research Progresses of Garnet-Type Solid Electrolytes for Developing All-Solid-State Li Batteries - Kim, Abin; Woo, Seungjun; Kang, Minseok; Park, Heetaek; Kang, Byoungwoo (Frontiers in Chemistry, 2020)
Demands for Li-ion batteries (LIBs) with high energy density and superior safety have been increasingly grown. To meet strong demand, all-Solid-State Batteries (ASSB) based on oxide-based solid electrolytes (SEs) have been considered as a promising energy storage platform. However, the realization of ASSB and its practical utilization in applications are very challenging because of high interfacial resistance between particles in a composite electrode and between electrodes and the use of Li metal as an anode. In this paper, we overview recent research progresses on oxide-based SEs for the ASSB with respect to the use of Li metal. Especially, we focus on research progresses on garnet-type solid electrolytes (Li7La3Zr2O12) because they have high ionic conductivity, good chemical stability with Li metal, and wide electrochemical potential window. This review will be also discussed about Li dendritic behavior in the oxide-based SEs and its relationship with critical current density (CCD). We will close this review with remarks on the prospects of ASSB.